2013
DOI: 10.1159/000350923
|View full text |Cite
|
Sign up to set email alerts
|

Combining Analyses of Basophil Allergen Threshold Sensitivity, CD-sens, and IgE Antibodies to Hydrolyzed Wheat, ω-5 Gliadin and Timothy Grass Enhances the Prediction of Wheat Challenge Outcome

Abstract: Background: Wheat is a common food causing allergy which has implications on the quality of life. The diagnosis of IgE-mediated wheat allergy is based on the clinical history and presence of IgE antibodies (IgE-Ab) in skin or blood, and the results of an oral food challenge which is time consuming and associated with risks. An improved diagnostic workup is needed for wheat allergy. The objective was to examine the relationship between wheat challenge, CD-sens and IgE-Ab to related allergens in wheat-allergic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…Considering CD-sens, a correlation was detected for CD203c but not CD63. Thus, the BAT can be used as a functional assay to detect sensitization status, which had been shown previously [26]. However, in our hands, CD203c seems to be superior compared to CD63.…”
Section: Discussionsupporting
confidence: 68%
“…Considering CD-sens, a correlation was detected for CD203c but not CD63. Thus, the BAT can be used as a functional assay to detect sensitization status, which had been shown previously [26]. However, in our hands, CD203c seems to be superior compared to CD63.…”
Section: Discussionsupporting
confidence: 68%
“…Many wheat-allergic individuals have been shown to be sensitized to a-, b-, c-, and/or x-gliadins as well as high and low molecular weight glutenins (HMW-glutenin and LMW-glutenin, respectively) (8)(9)(10)(11). Several studies have demonstrated that IgE-ab to x-5 gliadin is associated with wheat allergy, both wheatdependent exercise-induced anaphylaxis (WDEIA) in adolescents and adults (10,12) and immediate allergic reactions to wheat in children (13)(14)(15)(16)(17). However, the latter has not been confirmed in all studies (18).…”
mentioning
confidence: 99%
“…The provocation outcome of wheat-sensitised patients could be predicted with a combination of basophil sensitivity and s-IgE to wheat allergen [55]. Spontaneous CD203c expression on blood basophils and basophil reactivity correlate with the degree of tolerance among patients with cow's milk allergy [56].…”
Section: Progress In the Diagnosis And Monitoring Of Allergy By Basopmentioning
confidence: 99%